1998
DOI: 10.2166/wqrj.1998.031
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Fatty Acids Production by Anaerobic Whey Permeate Biodegradation in a Continuous Bioreactor

Abstract: This paper addresses the production of volatile fatty acids with fermentation of whey permeate under acidogenic conditions. The coal-immobilized biomass of an anaerobic fluidized bed reactor operated with a fairly constant hydraulic residence time of 12 min transformed the substrate (whey permeate i.e., essentially lactose) into a blend of acetic, propionic, butyric and isobutyric acids corresponding to between 2 and 19, 1 and 6, 11 and 30, 0 and 2% of the initial load (carbon basis), respectively. There was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Acetic, propionic, n-butyric and n-valeric acids were commonly produced during acidogenesis of dairy wastewater. Anaerobic production of volatile fatty acids (VFAs) with fermentation of whey permeate (wastewaters from cheese-making process) was investigated in a laboratory-scale anaerobic fluidized bed reactor [107]. It has been shown that up to 19% of the initial sugar was converted to volatile acids.…”
Section: Two-phase Anaerobic Treatment Of Dairy Wastewatermentioning
confidence: 99%
“…Acetic, propionic, n-butyric and n-valeric acids were commonly produced during acidogenesis of dairy wastewater. Anaerobic production of volatile fatty acids (VFAs) with fermentation of whey permeate (wastewaters from cheese-making process) was investigated in a laboratory-scale anaerobic fluidized bed reactor [107]. It has been shown that up to 19% of the initial sugar was converted to volatile acids.…”
Section: Two-phase Anaerobic Treatment Of Dairy Wastewatermentioning
confidence: 99%
“…This is not the case for water used in this study because dairy wastewaters contains butyric and caproic acids as soluble volatile fatty acids but not acetic or propionic acids (Mokrani, 1995). According to Imbeault (1997), initially, dairy wastewaters are characterized by an absence of VFAs.…”
Section: Influence Of Carbon Substrate Additionmentioning
confidence: 99%
“…Οξικό, προπιονικό, n-βουτυρικό και n-βαλερικό οξύ παράχθηκαν κυρίως κατά την οξυγένεση. Η αναερόβια παραγωγή πτητικών λιπαρών οξέων (VFAs) από την ζύμωση τυρόγαλου σε εργαστηριακής κλίμακας αντιδραστήρα ρευστοστερεάς κλίνης εξετάστηκε από τους Imbeault et al (90). Οι συγγραφείς έδειξαν ότι μέχρι και 19% των αρχικών σακχάρων μετατράπηκε σε πτητικά οξέα.…”
Section: αναερόβια επεξεργασία αποβλήτων σε δύο στάδιαunclassified